AN ANALYSIS OF THE TYPES OF GRAMMATICAL COHESION USED IN ESSAY WRITING APPLIED BY THE THIRD SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM AT SEKOLAH TINGGI KEGURUAN DAN ILMU PENDIDIKAN MUHAMMADIYAH KOTABUMI ACADEMIC YEAR 2018/2019 - Eva Rahayu (STKIP PGRI Lubuklinggau, 2019)
This research aimed to find out what are the types of grammatical cohesion used in essay writing applied by the third semester students of English education study program at Sekolah Tinggi Keguruan dan Ilmu Pendidikan Muhammadiyah Kotabumi (STKIP). The participant of the research consist of 52 active the students, and then the researcher chooses 5% score consist of the highest and lowest of the total number of the students to represent the subject in the research. This research used descriptive qualitative method. Then, the data collecting technique in this research was by using the document as the way to collect the data. Furthermore, the data are in written form in the form of essay writing. The researcher collected the data by finding the types of grammatical cohesion used in essay writing, selecting grammatical cohesions which were filled in the text based on characteristics of kinds of the grammatical cohesion, namely references, substitutions, ellipsis, and conjunction. The result of analysis showed that there are 206 items of the grammatical cohesions used in essay writing students. In references, it was found 64 items. Then, in substitutions it was found 2 items. Next, in ellipsis it was found 1 items. The last, in conjunction it was found 139 items.